Ancient Terminologies for Illnesses and Conditions in English Literary Texts (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the representation of illnesses and medical conditions in English literary texts through the lens of ancient terminologies. By examining a range of literary works spanning different historical periods, the study delves into the ways in which diseases and ailments were conceptualized and described in ancient times, and how these representations have influenced the language and understanding of illness in literature. Drawing on a diverse selection of texts, the article analyzes the use of archaic medical terminology and its impact on the portrayal of physical and mental afflictions. Furthermore, it investigates the cultural and historical contexts that shaped the language of illness in literature, shedding light on the evolution of medical terminology and its significance in literary expression. Through this exploration, the article aims to offer insights into the intersection of language, literature, and medical discourse, providing a deeper understanding of how ancient terminologies continue to resonate in contemporary literary representations of health and disease.